Effect of the high-pressure assisted-infusion processing on nutritional and antioxidantproperties of mango cubes - Perdomo Lamilla, Carolina (2021)
The aim of this work was to evaluate the effect of the high-pressure assisted-infusion processing on the nutritional and functional properties of mango cubes immersed in a solution of sorbitol and calcium lactate. Three factors were studied: sorbitol concentration (20°Brix-40°Brix-60°Brix), calcium lactate concentration (0% w/w − 1% w/w − 2% w/w) and the pressure level (0.1 MPa–300 MPa-600 MPa). Sugar (sorbitol, glucose and sucrose), calcium and total phenols content and antioxidant capacity were determined. Results showed that the increase of sorbitol concentration from 20°Brix to 40°Brix caused higher sorbitol uptake and lixiviation of the natural compo in mango cubes. However, the increase of sorbitol concentration from 40°Brix to 60°Brix, had no significant effect on the diffusion of solutes. The high-pressure processing (HPP) favored the diffusion of solutes from solution to fruit, while the addition of the calcium counteracted this effect in most cases. Based on these results, the combined effect of 300 MPa and 60°Brix-2% calcium lactate was the most effective at preserving natural compounds of mango and conferred distinctive properties giving an added value to the final product due to its important nutritional implications. Therefore, high-pressure assisted-infusion processing could be considered as an effective method to preserve mango cubes with an acceptable nutritional value. Industrial relevance The present work showed that high-pressure assisted-infusion processing could be considered an alternative to develop mango-based products. Results showed that this process would allow preserving most of the natural compounds of the mango pieces, in addition to achieving distinctive characteristics, as a source of calcium. Therefore, the application of high-pressure assisted-infusion processing could open new opportunities for food industries to develop fresh and value-added products with characteristics similar to fresh fruit.